Rāingān phon kānwičhai kānwičhai læ wāngphǣn phư̄a phatthanā kānsưksā khō̜ng ʻAmphœ̄ Mư̄ang Kānčhanaburī Čhangwat Kānčhanaburī. - Khrōngkān Wičhai læ Wāngphǣn phư̄a Phatthanā Kānsưksā (Thailand); Thailand. Samnakngān Khana Kammakān Kānsưksā hǣng Chāt ([Bangkok] : Samnakngān Khana Kammakān Kānsưksā hǣng Chāt, Samnak Nāyok Ratthamontrī, 1983)
Report on the Project to Develop Education in Kanchanaburi Province, Thailand.
Includes bibliographical references.
Keywords: Educational planning -- Thailand -- Kanchanaburi (Province)